Paleobiogeography of Lower-Middle Devonian Conulariids from southwest Gondwana - Rodrigues Ribeiro, Victor [UNESP]; Dowding, Elizabeth M.; Nascimento Sousa, Felipe [UNESP]; Augusto Carbonaro, Fábio [UNESP]; Pirani Ghilardi, Renato [UNESP] (Elsevier, 2023)
The bioregionalization of the Devonian fauna in southwest Gondwana has been extensively studied, focusing on the occurrences of brachiopods and trilobites, however, little attention has been given to Conulariids. The main goal of this paper is to propose a bioregionalization for the Conulariids (Conularia albertensis, C. quichua, C. sp., Paraconularia africana, P. ulrichana, and Reticulaconularia baini) from the Lower-Middle Devonian in southwest Gondwana. After a clustering analysis and diversity tests we have identified two distinct bioregions for Conulariids: the Amazon and southwest Gondwana, in the Amazon region the diversity is low, and can be attributed to scarcity of palaeontological data on the area. On the other hand, in the southwest Gondwana bioregion, diversity ranges from moderate to relatively high, which helps define a second-order bioregion, the Andeo-South Africa and Interior Gondwana. The first includes areas where diversity has higher values bordering southwest Gondwana (Bolivian Chaco-Peru, Zorritas-NOA-South Bolivia, South Africa and Malvinas areas). Further, in the Interior Gondwana bioregion are the Parnaíba (Parnaíba Basin), Alto Garças (north and northwest of Paraná Basin), Paraná (south of Paraná Basin, Uruguay and Paraguay) areas, where the diversity is slightly lower when compared to the Andeo-South Africa bioregion.
Keywords: Bioregion; Clustering; Diversity; Paleontology; South America